2004
DOI: 10.4088/pcc.v06n0403
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Neuropharmacology of Bupropion, a Dual Norepinephrine and Dopamine Reuptake Inhibitor

Abstract: BACKGROUND: The neurochemical and biological effects of antidepressant medications have become better defined over the last decade. When the anti-depressant bupropion was introduced in the United States in 1989, the specific pharmacologic basis of its clinical effects was uncertain. Research conducted over the past decade has significantly advanced the understanding of the neuropharmacology of bupropion and has demonstrated a novel mechanism of antidepressant activity. This article discusses the mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
311
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(336 citation statements)
references
References 73 publications
3
311
1
5
Order By: Relevance
“…Bupropion is approved for the treatment of depression and nicotine dependence, with a monoamine uptake inhibition effect (GlaxoSmithKline, 2004;Richmond and Zwar, 2003). Similar to stimulants such as cocaine, it can occupy the dopamine (DA) transporter to inhibit reuptake and increase DA concentration in the synaptic cleft (Stahl et al, 2004). It has been shown to be effective in improving symptoms of attention-deficit/hyperactivity disorder (ADHD) in adults (Wilens et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion is approved for the treatment of depression and nicotine dependence, with a monoamine uptake inhibition effect (GlaxoSmithKline, 2004;Richmond and Zwar, 2003). Similar to stimulants such as cocaine, it can occupy the dopamine (DA) transporter to inhibit reuptake and increase DA concentration in the synaptic cleft (Stahl et al, 2004). It has been shown to be effective in improving symptoms of attention-deficit/hyperactivity disorder (ADHD) in adults (Wilens et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion has relatively few antidepressant-associated side effects, such as sexual dysfunction and sedation (Stahl et al, 2004), has a low abuse potential (Nomikos et al, 1989), and is not fatal when taken in large doses (Shepherd et al, 2004). While bupropion's precise mechanism of action is not known, bupropion binds to DAT and has been shown to increase DA transmission in both the nucleus accumbens and the prefrontal cortex (Rau et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion is an antidepressant with stimulant properties (Stahl et al, 2004) that is effective for the treatment of nicotine dependence (Richmond and Zwar, 2003). In a clinical trial of bupropion for cocaine dependence (Margolin et al, 1995), an exploratory analysis suggested that patients with greater levels of depression may have benefited the most.…”
Section: Introductionmentioning
confidence: 99%